2019
DOI: 10.1021/acs.energyfuels.8b03376
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Modification and Adsorption Characteristics of Imidazole-Based Ionic Liquid on Carbonate Rock: Implications for Enhanced Oil Recovery

Abstract: Carbonate reservoirs contain a significant amount of oil and gas reserves, but the ultimate recovery of these reserves is very low because of higher wettability of the carbonate rock relative to crude oil. Surfactant flooding is the most common method employed to increase the recovery with the main mechanism of wettability alteration, which to an extent depends on the mineralogical attributes of the reservoir. Ionic liquid (IL), which acts as a surface-active chemical, was employed to investigate its potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Sessile drop experiments were performed to find out the effect of CSNs on the alteration of the wettability. 65 It was found that the contact angle reduced when the surfactant and polymer were added to the solution and then decreased further upon the addition of nanoparticles to the solution. The contact angle was measured at a different time interval, and it was found to be decreasing with time ( Figure 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sessile drop experiments were performed to find out the effect of CSNs on the alteration of the wettability. 65 It was found that the contact angle reduced when the surfactant and polymer were added to the solution and then decreased further upon the addition of nanoparticles to the solution. The contact angle was measured at a different time interval, and it was found to be decreasing with time ( Figure 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Possible synergistic effects with US should be evaluated as it could hasten the time of separation. Similar studies on the improved tertiary oil recovery should be considered as these solvents have been utilized in flooding agents and surfactants for altering the interfacial properties of emulsions [107] , [108] , [109] , [110] , [111] , [112] , [113] , [114] , [115] .…”
Section: Prospects and Future Trendmentioning
confidence: 99%
“…The more hydrophilic rock samples show greater imbibition heights during both Stage I and Stage III. According to the analysis, a more hydrophilic rock sample results in a smaller wetting angle of the liquid-solid interface [41]. Also, a greater capillary force results in a faster increase in imbibition height and greater overall imbibition height.…”
Section: Geofluidsmentioning
confidence: 99%